Pelatihan Quoting, Paraphrasing dan Summarizing untuk Menghindari Plagiat bagi Mahasiswa Program Magister Pendidikan Bahasa Inggris FKIP Universitas Mataram - Lalu Thohir; Nawawi Nawawi; Muhammad Amin; Mh. Isnaini (Universitas Mataram, 2023)
Plagiarism or plagiarism in the academic world is considered a crime because it steals other people's copyrights. Universities as mandated by the regulation of the Minister of National Education of the Republic of Indonesia No. 17 of 2010 need to take precautions so that plagiarism does not occur and counteract plagiarism. Plagiarism activities carried out by academics, especially students, are due to their ignorance about plagiarism and strategies to avoid plagiarism. Among the strategies that can be used by a writer to avoid plagiarism is by quoting and paraphrasing and summarizing other people's information, opinions or ideas correctly. This community service activity was carried out in the form of training which began with the delivery of material related to plagiarism, quoting, paraphrasing and summarizing to 17 students of the English language education master's study program at FKIP University of Mataram who were and would be completing their final assignment (thesis writing). This service activity was carried out in 2 meetings, where the first meeting was for delivering material and guided training and the second meeting was for presenting results and giving feedback, as well as evaluating activities. Based on the results of observations, questionnaires and portfolios, it can be concluded that students were enthusiastic in participating in a series of activities, active in asking questions, working in groups and presenting the results of their group work. The students also said that activities like this were very useful and hoped that similar activities would be held regularly.